1994
DOI: 10.1038/ng0994-88
|View full text |Cite
|
Sign up to set email alerts
|

Length of uninterrupted CGG repeats determines instability in the FMR1 gene

Abstract: Analysis of 84 human X chromosomes for the presence of interrupting AGG trinucleotides within the CGG repeat tract of the FMR1 gene revealed that most alleles possess two interspersed AGGs and that the longest tract of uninterrupted CGG repeats is usually found at the 3' end. Variation in the length of the repeat appears polar. Alleles containing between 34 and 55 repeats, with documented unstable transmissions, were shown to have lost one or both AGG interruptions. These comparisons define an instability thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
383
1
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(409 citation statements)
references
References 33 publications
21
383
1
3
Order By: Relevance
“…24 The vast majority of alleles with o45 CGG in the general population have repeat tracks with two AGG interruptions, and repeat instabilities are rare for these alleles. Data reported in the literature show that IA present similar proportions of unstable transmissions.…”
Section: Discussionmentioning
confidence: 99%
“…24 The vast majority of alleles with o45 CGG in the general population have repeat tracks with two AGG interruptions, and repeat instabilities are rare for these alleles. Data reported in the literature show that IA present similar proportions of unstable transmissions.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a family history of fragile X, however, risk assessments are problematic because some newly identified intermediate and small premutation alleles are stably inherited. 9 In 1994, Eichler et al 11 suggested that AGGs interspersed within the FMR1 repeat region increase its stability. In the general population, 94% of alleles have one or two AGG interruptions, which are most commonly observed on the 5′ end of the repeat tract as the 10 th or 11 th and 20 th or 21 st triplet of the repeat.…”
Section: Introductionmentioning
confidence: 99%
“…In intermediate and premutation alleles the AGG interruptions tend to occur at the 5' end of the locus and the pure CGG stretch, defined as the longest stretch of uninterrupted CGG repeats, is located at the 3' end (8,9). The loss of AGG interruptions appear to have occurred multiple times during human evolution (10) but can be a late event in the mutation pathway that leads to expansion (11).…”
Section: Introductionmentioning
confidence: 99%